Vitamin E and Cardiovascular Disease - Marchioli, Roberto (Thrombosis and Haemostasis, 2001)
Interest in the use of antioxidants for the treatment of human disease, and in the role of dietary antioxidants in the prevention of disease development, has been sustained for at least two decades. Several anti-oxidant protective mechanisms exist and constitute a primary defensive system including enzymatic defences (glutathione peroxidase and superoxide dismutase, which depend on the presence of ions such as selenium, zinc, copper, and manganese) and naturally occurring vita-mins such as vitamin E, vitamin A, beta-carotene, and vitamin C. The most important natural antioxidants are vitamin E (in the form of α-, β-, γ-, and δ-tocopherols), beta-carotene, vitamin C and selenium (fundamental constituent of glutathione-peroxidase, i.e., an enzyme with antioxidant function). The first two are lipophilic substances whilst ascorbic acid is hydrophilic. Each antioxidant has a different important mechanism of action since oxidative damage can be caused by lipid- or water-soluble molecules. Lipid-soluble antioxidants are likely to be very important in preventing the peroxidation of low-density lipo-proteins (LDL) and this action could be paramount in the prevention of atherosclerosis. On the other hand, water-soluble antioxidants could be useful where a water-soluble oxidative stress occurs (e.g., inflammation). As lipophilic molecules, vitamin E and beta-carotene are incorporated into the LDL particle. Vitamin E is the main lipid-soluble chain-breaking antioxidant in plasma and tissues and converts the peroxyl-free radical to hydroperoxide, a less reactive radical. It acts as a first-line anti-oxidative defence of LDL particles, protecting unsatu-rated fatty acids from peroxidation. Beta-carotene is a carotenoid (precursor of vitamin A, pro-vitamin) that acts as scavenger of oxidising radicals such as singlet oxygen and is a second-line antioxidative defence of LDL cholesterol. Vitamin C (ascorbic acid) can react with singlet oxygen, superoxide, hydroxyl radicals, and is the first line of antioxi-dative defence in water-soluble compartments. In addition, it plays an important role in regenerating reduced -tocopherol.